Multilayer radiating structures for mmWaves - Ramos, Amélia da Silva (2019)
In this dissertation three Yagi-Uda antennas were built, one with a frequency of operation of 2.4 GHz and the others operating at 24 GHz. Yagi-Uda antennas are well known, but here, printed Yagi-like prototypes were developed since nowadays most systems require printed circuits. Moreover, a comparison on the performance of a planar and a multilayer Yagi antenna was made, both operating in the mmWave region. Throughout the work it was possible to progressively improve gain and bandwidth, starting in the 2.4 GHz antenna and culminating in the multilayer prototype. These results were achieved without damage of the antennas’ global efficiency, which was kept at quite satisfactory values.